Efficacy and safety of corticosteroids in critically ill patients: a systematic review and meta-analysis - Lei Cao; Yingying Xiang; Zhuoxi Wu; Qi Chen; Fang Chen; Guiying Yang; Hong Li (BMC Anesthesiology)
Abstract Background The overall benefits and potential risks of corticosteroids, frequently administered to critically ill patients remain uncertain. This systematic review and meta-analysis evaluated the efficacy and safety of corticosteroid therapy in critically ill patients with severe community-acquired pneumonia, sepsis or septic shock, or acute respiratory distress syndrome. We hypothesized that corticosteroids reduce short-term mortality in critically ill patients. Methods We performed a search of Medline, Embase, and the Cochrane Central Register of Controlled Trials from database inception up to November 30, 2024. The search was limited to randomized controlled trials in human populations published in English. Dichotomous outcomes are reported as relative risk (RRs) and continuous outcomes as mean differences (MDs), both with 95% confidence intervals (CIs). The primary outcome was short-term mortality (28-day or nearest reported). Secondary outcomes included ICU/hospital length of stay, mechanical ventilation duration, ventilator-free days at 28 days, oxygenation index, reversed shock in sepsis or septic shock, and adverse events. We evaluated heterogeneity using I2 and explored it using subgroup and meta-regression analyses. Results Forty-three randomized controlled trials (n = 10853) were included. Corticosteroids reduced short-term mortality in critically ill patients compared to placebo (RR, 0.85; 95% CI, 0.77–0.94). Corticosteroid treatment for critically ill patients reduced intensive care unit (MD, − 2.02 days; 95% CI, − 3.14 – −0.90) and hospital (MD, − 2.66 days; 95% CI, − 4.58 – −0.74) lengths of stay, and duration of mechanical ventilation (MD, − 4.24 days; 95% CI, − 6.38 – −2.10); it increased ventilator-free days at 28 days (MD, 2.83 days; 95% CI, 1.20–4.47), improved oxygenation index (PaO2/FiO2) in patients undergoing mechanical ventilation (MD, 61.41 mmHg; 95% CI, 26.64–96.18), and reversed shock in sepsis or septic shock (RR, 1.20; 95% CI, 1.06–1.35). No significant differences were observed in infection rates (RR, 1.01; 95% CI, 0.92–1.12) and gastrointestinal bleeding (RR, 1.07; 95% CI, 0.86–1.33). Hyperglycemia was more prevalent in the corticosteroid group (RR, 1.10; 95% CI, 1.06–1.14). Conclusions Subgroup analysis indicated that early initiation (≤ 72 h), low-dose (e.g., < 400 mg/day hydrocortisone equivalent), and prolonged (≥ 7 days) corticosteroid therapy was associated with reduced short-term mortality in critically ill patients with severe community-acquired pneumonia or acute respiratory distress syndrome. For septic shock, combination therapy (hydrocortisone plus fludrocortisone) may enhance efficacy. Clinical trial registration PROSPERO: CRD42024517843.